Humanização do espaço carcerário: uma análise das políticas públicas para oferta de trabalho e educação no sistema prisional de Minas Gerais - Isabel Regina de Souza Pereira (2017)
Brazil administers the fourth largest prison system in the world. Minas Gerais has the second largest prison population in Brazil with approximately 60,000 inmates. The present research sought to analyze the execution of the public policies directed to the provision of the right to labor and education to the custodians of the prison system from the state of Minas Gerais. Although the Constitution establishes Brazil as a State of Law, what is seen in criminal execution is a cruel and dramatic situation with practices that are in conflict with the Constitution and with the Law. The sentenced person is not treated as a subject of rights. Their fundamental rights are violated by the omission of the State that does not establish the public policies necessary for the preservation of their human dignity. Among the fundamental rights of the custodian are the right to education and labor. The analysis carried out in this study had as premise that work and education are rights of all sentenced and not favors granted only to those who demonstrate merit. In order to justify the importance of work in the formation of the subject who is serving a sentence of deprivation of liberty, we have recourse to the thought of Karl Marx, considering the class warfare as the motor of history and labor in its formative and transforming dimension, as an educational principle. Foucault's contribution had fundamental importance to explain the genesis, development and function of the prison, which since its inception has been used as an instrument of control, discipline and power. Fernández Enguita helped understanding the school as a scenario where a series of social-material practices occurs, in addition to the transmission and circulation of ideas. Also appealed to Thompson's discussions and questions about the difficulty of reconciling the functions of the sentence established by law, and Saviani's careful exposition about the history and relation between labor and education. There are several contributions from other authors who defended ideas related to the problem discussed here, which had fundamental importance for the reflections proposed in this study. The methodology used included document analysis, participant observation and questionnaire.